A Conceptual Review on Smart Homes - Sharma, A; Gupta, S; Mittal, M (International Journal of Computer Sciences and Engineering, 2025)
Internet of Things (IoT) is the one of the most trending topic for research which had made its spurt emergence in the industry with breathtaking implementations. Internet of Things applications are like a big blue ocean covering plenty of devices leading to a whole new ecosystem. Nowadays, one of the most enlightened applications of the Internet of Things is Smart Homes. This concept has made our homes more secure and smarter resulting in judicious use of resources as well as leading to a smarter sustainable development. Smart homes are one of the most reliable applications of Internet of Things making one’s surrounding easy to deal with. This paper covers conceptual study on Smart Homes with offered utility, features and potency